Deep Brain Stimulation in Tourette’s Syndrome - Fraint, Avram; Pal, Gian (Frontiers in Neurology, 2015)
Objective: Tourette’s syndrome (TS) is defined by one year of persistent motor and vocal tics. Often, the tics are refractory to conventional pharmacologic and psychobehavioral interventions. In these patients, deep brain stimulation (DBS) may be an appropriate intervention. This paper reviews different DBS targets in TS, discusses existing evidence on the efficacy of DBS in TS, highlights adverse effects of the procedure, discusses indications and patient selection as well as future directions for DBS in TS. Methods: A literature review searching PubMed database entries between 2000 and 2015. Search terms included “DBS in Tourette Syndrome”, “Deep brain stimulation in Tourette syndrome” and “Surgical management of Tourette Syndrome”. Results: Though there are no universally accepted guidelines defining ideal DBS candidates for TS, age, tic severity, and treatment refractoriness are important factors to consider in patient selection. A variety of targets exist for DBS in TS, but thalamic targets and GPi are the most widely studied. Psychiatric side effects that are target specific should be monitored closely and it is possible that these adverse effects may be resolved with programming. Small randomized controlled trials support the efficacy of DBS in TS. Conclusions: DBS for TS is safe and feasible, but large multi-center clinical trials are needed to determine the ideal target and optimal location within a particular target.